Advantages of the Blue InGaN/GaN Light-Emitting Diodes with an AlGaN/GaN/AlGaN Quantum Well Structured Electron Blocking Layer - Ju, Zhen Gang (2016)
InGaN/GaN light-emitting diodes (LEDs) with p-(AlGaN/GaN/AlGaN) quantum well structured electron blocking layer (QWEBL) are designed and grown by a metal–organic chemical-vapor deposition (MOCVD) system. The proposed QWEBL LED structure, in which a p-GaN QW layer is inserted in the p-AlGaN electron blocking layer, not only leads to an improved hole injection but also reduces the electron leakage, thus enhancing the radiative recombination rates across the active region. Consequently, the light output power was enhanced by 10% for the QWEBL LED at a current density of 35 A/cm2. The efficiency droop of the optimized device was reduced to 16%. This is much smaller than that of the conventional p-AlGaN electron blocking layer LED, which is 31%.